ANALISIS PERTANGGUNG JAWABAN KEUANGAN DALAM PERSPEKTIF PSAK NOMOR 45 UNTUK AKUNTABILITAS LAPORAN KEUANGAN PADA YAYASAN SEKOLAH DASAR RHEMA INDONESIA - Mulia Rahmah, SKom., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2019)
Transparency and accountability in the financial report is needed. Transparency and accountability is needed to enable the users of financial report to understand the condition of the company and be able to assess the performance of a company. Like business company, non-profit organizations also require transparency and accountability in the financial report. To promote transparency and accountability of nonprofit organizations financial report Indonesian Institute of Accountants has made PSAK No. 45 on non- profit organizations. This research was conducted at the Yayasan Sekolah Dasar Rhema Indonesia  which is one-one-for-profit entity. This study objective to identify and analyze the application of PSAK NO. 45 in preparing the  financial report of the Yayasan Sekolah Dasar Rhema Indonesia. The analytical method used is descriptive qualitative. This study  shows that Yayasan Sekolah Dasar Rhema Indonesia not prepare financial report based on PSAK No.45. Yayasan Sekolah Dasar Rhema Indonesia have limited human resources issues in preparing the financial report. Stakeholders of Yayasan Sekolah Dasar Rhema Indonesia should prepare financial report based on PSAK No. 45 to develop the transparency and accountability of it’s financial report